Rare diseases – a challenge for the medical world - Bokayeva, Kamila; Miraleyeva, Alua; Walkowiak, Dariusz (Journal of Medical Science, 2021)
The diagnosis and treatment of rare diseases have improved significantly in recent years. The length of the diagnosis, which from the point of view of patients and their caregivers was considered the "Achilles' heel" of the healthcare system, has significantly shortened in many cases. Nevertheless, as research shows, there is still much to be done regarding the knowledge of rare diseases among healthcare professionals. The processes of diagnosis and treatment, as well as their organisation, should be redefined.